Short-term effect of volume recruitment–derecruitment manoeuvre on chest-wall motion in Duchenne muscular dystrophy. (May 2017) - Meric, Henri; Falaize, Line; Pradon, Didier; Lacombe, Matthieu; Petitjean, Michel; Orlikowski, David; Prigent, Hélène; Lofaso, Frédéric
Because progressive respiratory muscle weakness leads to decreased chest-wall motion with eventual ribcage stiffening, the purpose was to compare vital capacity (VC) and contributions of chest-wall compartments before and after volume recruitment–derecruitment manoeuvres (VRDM) in Duchenne muscular dystrophy (DMD). We studied nine patients with DMD and VC lower than 30% of predicted. VRDM was performed using 15 insufflations–exsufflations of +30 to −30 cmH2 O. VC and three-dimensional chest-wall motion were measured, as well as oxygen saturation, transcutaneous partial pressure of carbon dioxide and the rapid shallow breathing index (respiratory rate/tidal volume) before (baseline) and immediately and 1 hour after VRDM. VC increased significantly immediately after VRDM (108% ± 7% of baseline, p = 0.018) but returned to baseline within 1 hour, and the rapid shallow breathing index increased significantly. The non-dominant side systematically increased immediately after VRDM ( p = 0.0077), and in the six patients with abnormal breathing asymmetry (difference >10% of VC) at baseline, this asymmetry was corrected immediately and/or 1 hour after VRDM. VRDM improved VC and reduced chest-wall motion asymmetry, but this beneficial effect waned rapidly with respiratory muscle fatigue, suggesting that VRDM may need to be repeated during the day to produce lasting benefits.